KUALITAS PERAIRAN TELUK AMBON DALAM BERDASARKAN PARAMETER FISIKA DAN KIMIA PADA MUSIM PERALIHAN I - Wisnu Arya Gemilang; Guntur Adhi Rahmawan; Ulung Jantama Wisha (Universitas Lambung Mangkurat, 2017)
Inner Ambon Bay water (TAD) is the last accumulation area from several rivers downstream, the input materials and compounds from the land and rivers have a contribution in the water quality condition changes so that it is very important to recheck the water quality condition sustainably. The purpose of this study is to determine the water quality characteristics based on physical and chemical parameters for the basic of the existing data during transitional season I. The temperature, pH, salinity and dissolved oxygen is measured by in situ, and employed TOA DKK water quality checker, therefore the total suspended solid (TSS), turbidity and fat oil is analyzed by laboratory. The result of this study shows that generally water quality in the TAD is still proportional to the standard quality of aquaculture and marine life, nevertheless, some parameters such as TSS and turbidity is not proportional to the standard quality for seagrass and corals due to the enhance of sedimentation inside TAD.